Review of the genus Amnihayesomyia Niitsuma (Diptera: Chironomidae: Tanypodinae), with descriptions of three new species from China - Hongqu, Tang; Niitsuma, Hiromi (Zootaxa, 2020)
Three new species of Amnihayesomyia are described from China: A. vittata sp. n. and A. tibetica sp. n. each based on the male and female adults, and A. subflava sp. n. based on the male adult. In addition, a key to the known males of this genus is provided.